FACTORS AFFECTING THE CHAIN LENGTH OF GROUP A STREPTOCOCCI : II. QUANTITATIVE M-ANTI-M RELATIONSHIPS IN THE LONG CHAIN TEST - Ekstedt, Richard D. (The Rockefeller University Press, 1960)
Minute amounts of M protein were detected in culture supernates of virulent Group A streptococci by type-specific inhibition of the long chain and the bactericidal tests for anti-M antibody. The amount of M protein that was detected by the inhibition of these biological systems was less than could be demonstrated by precipitation tests. All strains of streptococci rich in M protein which were studied formed long chains when grown in sufficient concentrations of anti-M antibody. Very low concentrations of anti-M antibody escaped detection by the long chain test when strains of excessive M protein content were employed. Under such conditions the bactericidal test detected anti-M antibody more sensitively than the long chain test owing to the smaller inoculum employed in the former method. The scission of streptococcal chains may be inhibited by union of antibodies with surface antigens other than M protein. Long chains were formed when M-negative, R-positive strains were grown in sera containing anti-R antibody.